The impact of tamil language to sinhala inscriptions in ancient sri lanka - Chandawimala, K. (University of Jaffna, 2012)
From the beginning of written history, there was an obvious combination of languages which represented various cultures. The uniqueness of cultural value of languages depends on the historical background and it was hard to find an unpolluted origin of language without incorporating with others languages. In Sri Lanka, most of the languages are of Indian origin and incorporate with other roots of Indian languages. When considering the historical aspects of this combination, inscription languages in ancient Sri Lankan society are more important. Inscription means an ancient way of communication of the state or some institutes and with the general public. Therefore, the language of inscription represents various cultural impacts on contemporary societies. Many Sri Lankan inscriptions were written by current scholarly language or general languages. These trends are based on emerging influence of cultural patterns. In Sri Lankan situation, Sinhala language was common in ancient inscription writing. But with the cultural combinations, Tamil language effect to the Sinhala inscriptions. Some Tamil words like Pernattu, Ulwadu, Welaykkara, Weriwalakkam, Meyakkappar, Adakkalam, Samakkattu, Angampadi were used as Tamil origin word in Sinhala inscriptions. Especially inscriptions like Girithale, Allewewa, Athurupolayagama, Welyakkara, reflected language combination of Sinhala or Tamil. Terms and grammar patterns were combined with these Indian origin languages. In few inscriptions which were written after the 8th Century A.D. reflected these influences. In this study, the main objective is to find these influences and discuss about the historical background of these trends.